Cathepsin B contributes to TNF-α–mediated hepatocyte apoptosis by promoting mitochondrial release of cytochrome c - Guicciardi, M. Eugenia (American Society for Clinical Investigation, 2000)
TNF-α–induced apoptosis is thought to involve mediators from acidic vesicles. Cathepsin B (cat B), a lysosomal cysteine protease, has recently been implicated in apoptosis. To determine whether cat B contributes to TNF-α–induced apoptosis, we exposed mouse hepatocytes to the cytokine in vitro and in vivo. Isolated hepatocytes treated with TNF-α in the presence of the transcription inhibitor actinomycin D (AcD) accumulated cat B in their cytosol. Further experiments using cell-free systems indicated that caspase-8 caused release of active cat B from purified lysosomes and that cat B, in turn, increased cytosol-induced release of cytochrome c from mitochondria. Consistent with these observations, the ability of TNF-α/AcD to induce mitochondrial release of cytochrome c, caspase activation, and apoptosis of isolated hepatocytes was markedly diminished in cells from CatB(–/–) mice. Deletion of the CatB gene resulted in diminished liver injury and enhanced survival after treatment in vivo with TNF-α and an adenovirus construct expressing the IκB superrepressor. Collectively, these observations suggest that caspase-mediated release of cat B from lysosomes enhances mitochondrial release of cytochrome c and subsequent caspase activation in TNF-α–treated hepatocytes.